Fault Identification System for Motor Cycle Using Malfunction Indicator Lamp LED Blinking Frequency Detection on Mobile Device - Kedambadi, Monish Sanjay; Parmar, Manojkumar Somabhai; Doshi, Sagar Aswin (2018 International Conference on Advances in Computing, Communications and Informatics (ICACCI), 2018)
In any motorcycle with an electronic engine management system, malfunction indicator (MIL) lamp is provided to indicate faults. However, the amount of space available on the instrument cluster restricts the ability to identify some distinct faults. A mechanic would hence spend much time finding the exact cause of a fault. In the proposed system, the Electronic Control Unit (ECU) is modified to perform diagnosis of the vehicle and control the blinking pattern of the LED. By blinking the LED at different frequencies, a number of faults indicated using a MIL is increased. The value of blinking frequency is then calculated using a smartphone running an algorithm discussed herein this paper. The proposed system can be used on all motorcycles as the concept is a software-based algorithm, with minimal hardware modification. The building of a fault identification system is dependent on the technical performance of a frequency detection method/algorithm.